Relations - Marquez-Uppman, Julia, author; Vara, Vauhini, advisor; Candelaria Fletcher, Harrison, committee member; DeMirjyn, Maricela, committee member (Colorado State University. Libraries, 2024)
This memoir-in-essays explores questions of family, grief, and identity through various formal innovations. The first few essays examine identity formation through the concepts of place, lineage, inheritance, and home. In the latter half of the collection, the essays then shift to deeper questions of relationality, interdependence, and art (storytelling, music-making) as modes of constructing the self.